KONSTRUKSI KURIKULUM PESANTREN IBNUL AMIN MENURUT PEMIKIRAN MAHFUZ AMIN - ., Rahmadi (Pascasarjana UIN ANTASARI Banjarmasin, 2010)
This paper tries to explore the basic principality of Mahfuz Amin thought in constructing the curriculum of Ibnul Amin Pesantren, analyzed through the curriculum developing concept, namely: (1) the basic of the curriculum (religion, philosophy, sociology, and philosophy); (2) the principle of the curriculum; and (3) the orientation of the curriculum. The curriculum product from the thought of Mahfuz Amin is the curriculum that have the orientation to tafaqquh fi al-dn and takhasshus dn conservationally and traditionally with the goal to make life the religion knowledge based on ahlus sunnah wal jamaah value.